Pengaruh Pembelajaran Daring terhadap Motivasi Belajar Siswa pada Pembelajaran Matematika di Sekolah Dasar - Sahabuddin Sahabuddin; Aliwar Aliwar; Raehang Raehang; Imaludin Agus (Diniyah: Jurnal Pendidikan Dasar, 2022)
This study aims to describe the online learning system at SDN 11 Ranomeeto, describe the level of fifth grade students' learning motivation when learning online, and analyze the effect of online learning on students' learning motivation in fifth grade mathematics learning. This research is a quantitative study with a survey approach. The research was conducted at SD Negeri 11 Ranomeeto with 22 students as respondents. Data collection techniques are observation, questionnaires, and documentation while data analysis techniques use descriptive analysis techniques and inferential analysis. The results of the study show that the online learning at SD Negeri 11 Ranomeeto V during the Covid-19 pandemic used the Whatsapp application. The level of student learning motivation is in the (moderate) category. The simple coefficient value (r) is 0.935 which means that there is a very strong relationship between online learning variables and learning motivation. The results of the coefficient of determination (KD) show that the influence of online learning variables on learning motivation is 87.5%, while 12.5% is influenced by other factors not discussed in this study.Keywords: Online learning, student’s learning motivation, elementary school